317 Non-fatal injuries untreated at hospitals in Hunan, China: implications for hospital-based surveillance systems. (1st September 2016) - Wu, Yue; Zhang, Wei; Zhang, Lin; Schwebel, David; Ning, Peishan; Cheng, Xunjie; Deng, Xin; Li, Li; Deng, Jing; Hu, Guoqing
Abstract : Background: Disability adjusted life year (DALY) is among the most commonly-used indicators of disease/injury burden. It relies on accurate data concerning non-fatal conditions, which may be collected through hospital-based surveillance or population-based surveys. To determine whether hospital-based surveillance captures all non-fatal injuries, we assessed the extent of non-fatal but serious injuries not treated at hospitals. Methods: Data from the first provincial health household interview survey of Hunan, China, conducted in 2013, were used. Injury events were identified when any of the following circumstances occurred in the prior 14 days: (1) hospital visit following an injury; (2) receiving medical treatment elsewhere for an injury (e.g., taking medications, or receiving massage or hot compress); and/or (3) being off work or school, or in bed for more than 1 day, following an injury. We calculated the proportion of injury events not treated at hospitals and reasons for not visiting hospital for injury events occurring during the previous two weeks. Results: We captured 108 injury events (56 during the previous two weeks and 52 at other times). The weighted injury prevalence was 4.9 per 1, 000 persons during the last two weeks (95% confidence interval: 2.9–6.9 per 1, 000 persons). Of the 56 events, 14 (weighted proportion 41.2%) were not treated at hospitals. Primary explanations for skipping hospital visits included perceiving injuries were too minor and economic limitations to travel to hospitals or seek treatment. Conclusions: Results imply the burden of non-fatal injury may be underestimated by hospital-based surveillance systems such as that used in China.